Chrysin reduces proliferation and induces apoptosis in the human prostate cancer cell line pc-3 - Saeed Samarghandian; Jalil Tavakkol Afshari; Saeideh Davoodi (Clinics, 2011)
INTRODUCTION: Honey is a common household product with many medicinal uses described in traditional medicine. Only recently has its antioxidant properties and preventive effects against disease been highlighted. Chrysin is a natural flavone commonly found in honey that has been shown to be an antioxidant agent. In this study, we investigated the antiproliferative and apoptotic effects of honey and chrysin on cultured human prostate cancer cells. METHODS: Cells were cultured in RPMI medium and treated with different concentrations of honey and chrysin for three consecutive days. Cell viability was quantitated by the 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay. The percentage of apoptotic cells was determined by flow cytometry using Annexin V-fluorescein isothiocyanate. RESULTS: The MTT assay revealed that both compounds had an antiproliferative effect on PC-3 cells in a dose- and time-dependent manner. The IC50 values for honey and chrysin against PC-3 cells were 2.5% and 24.5% after 48 h and 1.8% and 8.5% after 72 h, respectively. Chrysin induced apoptosis in PC-3 cells, as determined by flow cytometry. CONCLUSION: Our results suggest that honey has anti-proliferative effects on prostate cancer cells and the effects are mainly due to chrysin. Therefore, chrysin may be a potential compound for both cancer prevention and treatment. Further in vivo investigation is needed to support the use of chrysin in cancer therapy.